Konstruk Teori dan Paradigma Pengetahuan - R, Rahmawati; M, Marilang; Nonci, M. Hajir (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The development of science involves constructing theories and adopting paradigms as intellectual foundations in formulating research frameworks. Theories, consisting of interconnected concepts, definitions, propositions, and variables, provide a systematic perspective on phenomena and aim to explain and predict observed phenomena. Paradigms, as patterns of thought or general reference frameworks, guide how scientists understand, approach, and interpret reality. This study explores the essence of theory construction in the development of science, examining the role of theory in explaining, predicting, and controlling phenomena. Meanwhile, the concept of paradigm is introduced as a philosophical foundation shaping the scientific perspective and creating a shared framework of understanding within a research community. Through a profound understanding of theory construction and paradigm in knowledge development, we can appreciate how the evolution of knowledge and scientific worldviews unfolds. This study offers insights into the crucial roles of theory and paradigm in guiding knowledge exploration, emphasizing their relevance in addressing the dynamics of complexity and variation in scientific phenomena.